Viscosity‐curing time behavior, viscoelastic properties, and phase separation of graphene oxide/epoxy asphalt composites. Issue 8 (29th June 2022) - Zhao, Ruikang; Jing, Fan; Li, Chenxuan; Wang, Rui; Xi, Zhonghua; Cai, Jun; Wang, Qingjun; Xie, Hongfeng
Abstract: Graphene oxide (GO) with 0.2, 0.5, and 1.0 wt% loading was used to modify warm‐mix epoxy asphalt binders (WEABs). The thermal stability, structure of GO, rotational viscosity‐curing time performance, dynamic moduli, glass transitions, damping ability, mechanical performance, and phase‐separated morphology of GO/epoxy asphalt composites were investigated in the laboratory. GO significantly enhanced the thermal stability of the pure WEAB. X‐ray scattering analysis revealed that GO layers were delaminated in the epoxy asphalt binder. GO accelerated the cure reaction of the pure WEAB and thus resulted in higher rotational viscosity of GO/epoxy asphalt composites. Furthermore, the viscosity of the modified WEABs slightly increased in the GO content. GO increased the dynamic moduli and T g s of both epoxy and asphalt for the pure WEAB. However, the damping ability of GO/epoxy asphalt composites was similar to that of the pure WEAB. Confocal microscopy observations revealed that GO was dispersed in both asphalt and epoxy phases of the phase‐separated WEAB. The asphalt domains in the continuous epoxy phase became more spherical and uniform with the existence of GO. Moreover, the dispersion of epoxy in the discontinuous asphalt phase became more evident. The mechanical properties of the pure WEAB were greatly improved with the addition of GO. The tensile toughness and strength of the pure WEAB increased by 31% and 33%, respectively, with the addition of 0.2 wt% GO.